Socio-economic determinants of public healthcare - Mykola Melnyk; Andriy Blyznyukov; Svitlana Kolomiiets; Ruslan Dinits (Health Economics and Management Review)
The main socio-economic mission of the healthcare system is to participate in the formation of workforce, strengthen the labor potential of society, and promote economic growth. The national health serves as an important economic resource. The COVID-19 pandemic has proven that losses due to illness and absence of employees from the workplace have negative economic consequences. The bibliometric study conducted via the VOSViewer bibliometric analysis of Scopus publications in 2014-2024 for the query “socio-economic determinants of public healthcare” allowed to structure the scientific work within 8 clusters. The latter showed leading researchers from the USA, the UK, India, Australia, Canada, Germany, Italy and Spain. In 2020-2023, due to the pandemic, publication activity in this area increased significantly. The article conducts a regression analysis of the impact of socio-economic determinants on the level of public healthcare. The public healthcare index is the population life expectancy. Among socio-economic determinants, there are nine components as factor attributes: current healthcare expenditures per capita; income shares of the richest and poorest – 10% and 20%; mortality rates up to 5 years and from suicide; number of people using at least basic sanitation and safe drinking water services, etc. The data for Ukraine from the World Bank statistical base for 2002-2019 were used as an information fundament. The multiple regression generation by the method of stepwise exclusion of variables was implemented using the MS Excel software. The article formulates a list of recommendations for increasing life expectancy. It includes measures to ensure the sanitary and epidemiological well-being of the population, development of healthcare infrastructure. The research also ensures availability of medical services to the population. The study educates and informs the population about the hygiene importance, proper use of sanitation and the consequences of inadequate sanitary conditions for health. Relevance of affordable sanitation improvement programmes for the poor is discussed.